Expanding role for radiotherapy in metastatic non-small cell lung cancer in the era of targeted therapy and immuno-oncology - Luterstein, Elaine; Lee, Percy (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Radiotherapy for advanced stage non-small cell lung cancer (NSCLC) has traditionally been administered with palliative intent. However, an emergence of data from retrospective studies and, more recently, prospective trials has indicated the potential of using stereotactic ablative radiotherapy (SABR), in combination with known cytotoxic therapies, targeted therapies, and immunotherapeutic agents, to play a curative rather than palliative role in targeting sites of oligometastatic disease. Analysis of patterns of failure for oligometastatic NSCLC after first-line systemic therapy has revealed that failure occurs prevalently at sites of gross disease present at baseline rather than at new disease sites (1), and it has been postulated that local ablation of metastases could limit progenitor sites of new metastatic spread and extend progression free survival (PFS).